Pendapatan Per Kapita dan Suku Bunga Deposito Berpengaruh Signifikan terhadap Jumlah Simpanan Deposito pada Bank Umum di Kota Cirebon - Jajuli Jajuli; Nunik Kadarwati; Agus Arifin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
This research is aimed to understand the increasing of deposit account of commercial bank in Cirebon which is seen from the increasing of income percapita in Cirebon, offered deposit account interest rate by bank, and inflation rate in Cirebon. This research was executed by descriptive and quantitative method. Data was obtained from Bank Indonesia of Cirebon, Badan Pusat Statistik (BPS) of Cirebon, and the period of time which is used in this research was during 2001–2007. This research used Natural Logarithmic Multiple Regression Analysis, Classical Assuming Test, and Elasticity test. Regarding to the result of natural logarithmic multiple analysis estimation, it can be concluded that significantly income percapita, deposit account interest rate, and inflation simultaneously affecting deposit account values of commercial bank in Cirebon, meanwhile, partially income percapita and deposit account interest rate significantly affecting deposit account values of commercial bank in Cirebon, and inflation in Cirebon did not give any significant affect toward deposit account values of commercial bank in Cirebon. Regarding to Elasticity test, income percapita is the most affecting variable toward deposit account value of commercial bank in Cirebon. Keywords: deposit account, income percapita, interest rate, inflation